The Dynamics of Argumentation and Critical Thinking in Arabic Debate at Ma'had Al-Jami'ah - Fuad Hilmi, Annafik; Aziz, Abdul; Daroini, Slamet (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the dynamics of argumentation and critical thinking in Arabic debate practice within the Ma'had Al-Jami'ah Central Debate Team. In contrast to previous studies which focused more on the technical aspects of debate or individual abilities separately, this research positions debate practice as an integrative space for the development of reasoning and language skills. Using a descriptive qualitative method with a case study approach and content analysis based on Lasswell's theory, the research findings indicate that the quality of argumentation is determined not only by mastery of accurate material and data, but also by a systematic mindset developed through structured preparation and continuous practice. Critical thinking plays a key role in constructing logical arguments, anticipating weaknesses, and creating analogies that strengthen the debating position. The novelty of this study lies in the revelation that the dynamics of argumentation and critical thinking in Arabic debate are formed through the simultaneous interaction of three pillars: systematic preparation, data-based argument construction, and strengthening critical-reflective thinking patterns. The implication is that debate activities are not merely a linguistic competition, but also a strategic vehicle for the development of critical reasoning and scientific communication skills in students.